High-quality permanent draft genome sequence of the Mimosa asperata - nodulating Cupriavidus sp. strain AMP6. Issue 1 (December 2015) - De Meyer, Sofie; Parker, Matthew; Van Berkum, Peter; Tian, Rui; Seshadri, Rekha; Reddy, T.B.K.; Markowitz, Victor; Ivanova, Natalia; Pati, Amrita; Woyke, Tanja; Kyrpides, Nikos; Howieson, John; et al.
Abstract Cupriavidus sp. strain AMP6 is an aerobic, motile, Gram-negative, non-spore-forming rod that was isolated from a root nodule ofMimosa asperata collected in Santa Ana National Wildlife Refuge, Texas, in 2005.Mimosa asperata is the only legume described so far to exclusively associates withCupriavidus symbionts. Moreover, strain AMP6 represents an early-diverging lineage within the symbioticCupriavidus group and has the capacity to develop an effective nitrogen-fixing symbiosis with three other species ofMimosa . Therefore, the genome ofCupriavidus sp. strain AMP6 enables comparative analyses of symbiotic trait evolution in this genus and here we describe the general features, together with sequence and annotation. The 7, 579, 563 bp high-quality permanent draft genome is arranged in 260 scaffolds of 262 contigs, contains 7, 033 protein-coding genes and 97 RNA-only encoding genes, and is part of the GEBA-RNB project proposal.